Mathematical Model of Maximum Commutation Half Cycle for Thermal Countercurrent Oxidation of Low-Concentration Gas in Coal Mine Ventilation - Kuan Wu; Shiliang Shi; Yong Chen (Shock and Vibration)
The Fluent computational fluid dynamics software was used to study the relevant factors affecting the maximum commutation half cycle for thermal countercurrent oxidation of low-concentration gas in coal mine ventilation. Based on orthogonal experiments, the maximum commutation half cycle for thermal countercurrent oxidation of the exhaust gas in the coal mine ventilation under 25 working conditions with the combination of different methane concentrations, inlet speeds, porosities, and oxidation bed filling lengths is investigated. SPSS data processing software was used to perform regression analysis on the numerical simulation data, and a mathematical model for predicting the maximum commutation half cycle under the influence of four factors was obtained. Through experiments, the mathematical model of the maximum commutation half cycle by the numerical simulation was verified. After introducing the wall heat loss correction coefficient, the complete prediction model of the maximum commutation half cycle was obtained. Comparing the experimental test value with the calculated value using the corrected model, the relative error was not more than 3%. The complete mathematical model corrected can be applied to the design calculation of the maximum commutation half cycle for thermal countercurrent oxidation of low-concentration gas in actual coal mine ventilation.